English language reading comprehension of Pakistani HSSC/HSC level students: performance and perceptions / Madiha Rehman and Muhammad Fareed - Rehman, Madiha; Fareed, Muhammad (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
English is taught as a compulsory subject from grade one to graduate level in Pakistan. It has also been given the status of the official language and is also considered a symbol of status. Good English language skills open up avenues to have access to high-ranking jobs both in the public and private sectors in Pakistan. Despite the importance of the English language in Pakistan, teaching the English language requires more focus and research. Even though reading skill is the most focused English language skill in the Pakistani school education, students face difficulties in reading comprehension. As English language reading skills are considered intricate, hence they require considerable time and practice to develop. Reading skills are important both for academic and professional purposes and the ability “to read” involves more than just decoding a text. Keeping in view the importance of reading comprehension skills, this research was designed to explore perceptions of HSSC/HSC students and teachers about teaching reading comprehension skills. This study also tested the reading comprehension skills of the selected HSSC/HSC students from the Federal Board of Intermediate and Secondary Education (FBISE) and the Board of Intermediate Education Karachi (BIEK). The sample of this study were 60 students - 30 from each board, and all (4) English language teachers of the selected college. Quantitative data for this study were collected through reading comprehension tests and qualitative data were obtained through focus group interviews from the students and HSSC English language teachers. The quantitative data were analyzed by using SPSS version 24 and thematic analysis for qualitative data were carried out as suggested by Saldana (2013). Although, The Findings revealed that students of the FBISE performed better than students of the BIEK in reading comprehension test, but, the perceptions of students unveiled that the performance of students was highly dependent on their interest to read the books, the content of their prescribed books, teachers’ guidelines and the vocabulary bank. The English language teachers added that students’ performance is not only dependent on their thirst to seek knowledge and their approach to read books but also students’ performance varies due to the content of the syllabus books and assessment of reading comprehension skills at the HSSC/HSC level.